Criminal justice and the placement of abused children - Martell, Diane R., 1957- (Criminal justice (LFB Scholarly Publishing LLC), 2005)
Annotation Child welfare, criminal justice, and law enforcement agencies recognize the importance coordinated, inter-agency practices to ensure the best outcomes for victims of child maltreatment. Martell examines if the separate interventions of the criminal justice system and child welfare system impact each other. Specifically, she studies the potential for an association between the criminal justice case prosecution and the protective service child placement decisions. The results indicate that, in some cases, criminal justice interventions can help to prevent the need for child removal. In addition, Martell explains how the presence of child neglect can be an important factor in whether or not a child abuse case is chosen for prosecution.